ECB Interventions in Distressed Sovereign Debt Markets: The Case of Greek Bonds - Christoph Trebesch; Jeromin Zettelmeyer (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper analyses the determinants and effects of ECB interventions in times of severe distress. We focus on the Greek government bond market in mid-2010 and use a unique new dataset to show, for the first time, what type of bonds the ECB bought. We then explore the short-term effects of ECB purchases at the bond-level. The results show a large impact of the interventions on the targeted instruments. Bonds bought by the ECB see a much steeper drop in yields than those not bought. This is consistent with theories of “local supply effects” in segmented or illiquid bond markets.
Keywords: E43; E58; F34; G12; 330; central bank; asset purchases; securities markets programme; Eurozone crisis; sovereign risk; market segmentation